The impact of knowledge management on the strategic performance in economic company (SOMIPHOS) Based on the third-generation Balanced Scorecard (BSC ΙΙΙ) - Hassine, Attman; Zine, Amrane (Milev Journal of Research and Studies, 2023)
This study as aim to identify the impact of knowledge management on strategic performance in SOMIPHOS. In order to achieve the objectives of the study, the questionnaire was used as a main tool in the collection of data analyzed by the SPSS. The study Submitted a set of results, The most important of which, is the existence of a statistically significant relationship of knowledge management to the strategic performance in the institution under study. The study also presented in light of the results of a set of recommendations related to this subject.